Oh, what a happy little math problem we have here! When you multiply 7x squared by x squared, you simply add the exponents together, giving you 7x to the power of 4. Isn't that just delightful? Just remember to keep those numbers and variables in order, and you'll create a beautiful equation every time.
When you do (7x)2, you square both numbers.So 7 squared=49 and x squared=x2Your answer should be 49x2Let's try another example: 2(3xy)3Now we cube each number in the parentheses. 2(33x3y3)=2(27x3y3)Finally you multiply the 2 and the 27. 54x3y3
(x - 5)(x + 12)
(x + 2)(x - 9)
2x2 + 7x - 15 = (2x - 3)(x + 5)
((15xy2)/(x2+5x+6))/((5x2y)/(2x2+7x+3)) =(15xy2/5x2y)*(2x2+7x+3)/(x2+5x+6) =(3y/x)*(((2x+1)(x+3))/((x+2)(x+3) =(3y(2x+1))/(x(x+2)) =(6xy+3y)/(x2+2x)
X squared + 7X + 12?
7x-x2 = x(7-x)
if its x(squared) its 7x(cubed) if its 2xX its 14x(squared)
Assuming that it is only the x that is being squared. (-21x^2)/39 = (-7x^2)/13
(7x - 10)(x + 1)
When you do (7x)2, you square both numbers.So 7 squared=49 and x squared=x2Your answer should be 49x2Let's try another example: 2(3xy)3Now we cube each number in the parentheses. 2(33x3y3)=2(27x3y3)Finally you multiply the 2 and the 27. 54x3y3
7x + 8
x(x - 7)
(x2 + 7x - 18) = (x + 9)(x - 2)
If you mean: x squared -7x +12 then it is (x-3)(x-4) when factored
x(x-7)
It is: x(x+7) when factorized